2022
DOI: 10.5468/ogs.22115
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic tranexamic acid to reduce blood loss and related morbidities during hysterectomy: a systematic review and meta-analysis of randomized controlled trials

Abstract: To perform a systematic review and meta-analysis of all randomized controlled trials (RCTs) that evaluated the efficacy and safety of prophylactic tranexamic acid (TXA) versus a control (placebo or no treatment) during hysterectomy for benign conditions. Six databases were screened from inception to January 23, 2022. Eligible studies were assessed for risk of bias. Outcomes were summarized as weighted mean differences and risk ratios with 95% confidence intervals in a random-effects model. Five studies, compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…TXA has also been proven to be effective to reduce blood loss in other gynaecological procedures. In a systemic review and meta-analysis of randomized controlled trial, Abu-Zaid et al reported that TXA is effective in reducing intraoperative blood loss, requirement for postoperative blood transfusion, and requirement for intraoperative topical hemostatic agents among patients undergoing hysterectomy [ 26 ]. TXA has also been proven to be effective and safe in reducing postpartum hemorrhage among parturients.…”
Section: Discussionmentioning
confidence: 99%
“…TXA has also been proven to be effective to reduce blood loss in other gynaecological procedures. In a systemic review and meta-analysis of randomized controlled trial, Abu-Zaid et al reported that TXA is effective in reducing intraoperative blood loss, requirement for postoperative blood transfusion, and requirement for intraoperative topical hemostatic agents among patients undergoing hysterectomy [ 26 ]. TXA has also been proven to be effective and safe in reducing postpartum hemorrhage among parturients.…”
Section: Discussionmentioning
confidence: 99%
“…TA has recently been shown to reduce haemorrhage in gynaecology illnesses like menorrhagia, hysterectomy, and myomectomy. Numerous researches examined the use of TA administration in caesarean section and found it to be effective (3,4).…”
Section: Introductionmentioning
confidence: 99%